Path Analysis on Factors Associated with the Risk of Scabies Among Students at Darussalam Islamic Boarding School, Blokagung, Banyuwangi, Indonesia - Febrika Devi Nanda; Bhisma Murti; Ruben Dharmawan (Masters Program in Public Health, 2016)
Background: Scabies is an infectious disease that is particularly important in populations with low socioeconomic level in developing countries. Scabies is not life-threatening so usually get treatment is low. But actually the chronic and severe scabies can cause dangerous complications. This study aimed to analyze factors associated the students with scabies disease.Subjects and Methods: This was an observational analytical study with cross-sectional design. This was conducted at Darussalam Islamic Boarding School of Blokagung Banyuwangi, Indonesia in March 23 to April 30,2016. A total of 90 samples were amounted 30 students with scabies and 60 had not scabies. Data collection was using questionnaire. Data analysis used STATA 13.Results: Four variables associated with scabies was associated indirectly obtained between knowledge and myth was negative amounting to the value of -1.88 (p < 0.001) path coefficient between knowledge and healthy behaviors is positive that amounting to 1.68 with value (p = 0.016), the path coefficient between myth - 2:39 (p = 0.038), the path coefficient between allowance to health behaviors positive value that is equal to 2:00 (p = 0.026), the path coefficient between health behavior with scabies is negative in the amount - 3:43 (p < 0.001).Conclusion: The level of knowledge, myths, pocket money indirectly related to the incidence of scabies through healthy behaviors. It is expected to reduce disease scabies students can change the behavior of health to be good.Keywords: scabies, level of knowledge, myths, pocket moneyCorrespondence: Febrika Devi Nanda. Bakti Indonesia University, Banyuwangi. Email: febrika_devinanda@yahoo.comJournal of Epidemiology and Public Health (2016), 1(1): 18-26https://doi.org/10.26911/jepublichealth.2016.01.01.03